The Effects of Candesartan on Left Ventricular Hypertrophy and Function in Nonobstructive Hypertrophic Cardiomyopathy: A Pilot, Randomized Study - Penicka, Martin (American Society for Investigative Pathology, 2009)
Hypertrophic cardiomyopathy is caused by mutations in the genes that encode sarcomeric proteins and is primarily characterized by unexplained left ventricular hypertrophy, impaired cardiac function, reduced exercise tolerance, and a relatively high incidence of sudden cardiac death, especially in the young. The extent of left ventricular hypertrophy is one of the major determinants of disease prognosis. Angiotensin II has trophic effects on the heart and plays an important role in the development of myocardial hypertrophy. Here in a double-blind, placebo-controlled, randomized study, we show that the long-term administration of the angiotensin II type 1 receptor antagonist candesartan in patients with hypertrophic cardiomyopathy was associated with the significant regression of left ventricular hypertrophy, improvement of left ventricular function, and exercise tolerance. The magnitude of the treatment effect was dependent on specific sarcomeric protein gene mutations that had the greatest responses on the carriers of ß-myosin heavy chain and cardiac myosin binding protein C gene mutations. These data indicate that modulating the role of angiotensin II in the development of hypertrophy is specific with respect to both the affected sarcomeric protein gene and the affected codon within that gene. Thus, angiotensin II type 1 receptor blockade has the potential to attenuate myocardial hypertrophy and may, therefore, provide a new treatment option to prevent sudden cardiac death in patients with hypertrophic cardiomyopathy.